Role of Contingency in Formation of International Law - О. S. Magomedova (Московский журнал международного права, 2023)
INTRODUCTION. A group of foreign international scholars has recently published a collective monograph – “Contingency in International Law: on the possibility of different legal histories” [Contingency in International Law…2021]. The starting point of this work is the question why international law is as we know it today, and whether it could be different. The problem of possible alternative ways for development of international law calls challenges the necessity of the current state of international law and urges to research the interrelation among the power of international law itself, historical context and wills of subjects involved in international law-creating.MATERIAL AND METHODS. The research material for the present article is the collective monograph “Contingency in International Law: on the possibility of different legal histories” edited by I. Venzke and K.J. Heller. The study of the presented ideas is based on general scientific methods and private legal methods, as the historical and legal approach.RESEARCH RESULTS. The development of a national international legal scholarship of the theory of international law sometimes needs an intellectual impulse, a bold statement of questions that challenge the dominant theoretical principles. In this regard, the question on the possibility of different ways of developing international law due to a variety of factors, could be a trigger for rethinking positivist attitudes in the Russian theory of international law. The intention in revising the classical theses does not imply rejection of established legal positions, but, on the contrary, it necessitates fruitful reflections on traditional tenets. This assumption is illustrated with the concept of the international legal policy of the state, which originates from the classical theory of coordination of wills, and at the same time makes a number of assumptions or explanations which could answer questions about contingencies in formation of international legal norms. Relying on the materials of the book edited by I. Venzke and K.J. Heller the article provides outlook on questions about chance and regularities in determining the content of international law, about role of context in the creation and development of international law, about the sovereign wills and role of contingencies and extra-legal factors in the concept of international legal policy.DISCUSSION AND CONCLUSIONS. In contrast to the theory of coordination of wills, which is based on strict positivist grounds, the concept of the international legal policy of State assumes influence of extra-legal factors for arrangement of international legal argumentation of States. For example, the problem of context is of great importance in determining the possibility of legitimizing certain international legal positions of State. The arguments of States as such with references to norms of international law remain fruitless outside certain context (including present content of international law, current state of international relations, topics on the international agenda). This is because legitimated legal norms fix the current results of coordination of wills among States, which depend on interaction of legal and nonlegal factors. But it is also important to understand limits of assumptions about impact of certain factors on the content of international law. So, on the one hand, the role of context should not be overestimated, since international law does not succumb to conjuncture, but develops consistently. At the same time, by studying international legal policies of States, one should avoid false determinism. It poses the risk to trace a wrong strategic line of State's legal arguments with over-shadowing ‘irrelevant’ facts. Thus, questions that open perspectives on seemingly solved problems make it possible to develop established doctrinal ideas in a new direction. However, it is necessary to take into account methodological limits of new assumptions for consistent development of contemporary national discipline of international law.